Celecoxib and Dimethylcelecoxib Block Oxidative Phosphorylation, Epithelial-Mesenchymal Transition and Invasiveness in Breast Cancer Stem Cells - Gallardo-Pérez, Juan C.; de Guevara, Alhelí Adán-Ladrón; García-Amezcua, Marco Antonio; Robledo-Cadena, Diana Xochiquetzal; Pacheco-Velázquez, Silvia Cecilia; Belmont-Díaz, Javier Alejandro; Vargas-Navarro, Jorge Luis; Moreno-Sánchez, Rafael; Rodríguez-Enríquez, Sara (Current Medicinal Chemistry, 2022)
Background: The major hurdles for successful cancer treatment are drug resistance and invasiveness developed by breast cancer stem cells (BCSC). Objective: As these two processes are highly energy-dependent, the identification of the main ATP supplier required for stem cell viability may result advantageous in the design of new therapeutic strategies to deter malignant carcinomas. Methods: The energy metabolism (glycolysis and oxidative phosphorylation, OxPhos) was systematically analyzed by assessing relevant protein contents, enzyme activities, and pathway fluxes in BCSC. Once identified as the main ATP supplier, selective energy inhibitors and canonical breast cancer drugs were used to block stem cell viability and metastatic properties. Results: OxPhos and glycolytic protein contents, as well as HK and LDH activities were several times higher in BCSC than in their parental line, MCF-7 cells. However, CS, GDH, COX activities, and both energy metabolism pathway fluxes were significantly lower (38-86%) in BCSC than in MCF-7 cells. OxPhos was the main ATP provider (>85%) in BCSC. Accordingly, oligomycin (a specific and potent canonical OxPhos inhibitor) and other non-canonical drugs with inhibitory effect on OxPhos (celecoxib, dimethylcelecoxib) significantly decreased BCSC viability, levels of epithelial-mesenchymal transition proteins, invasiveness, and induced ROS over-production, with IC50 values ranging from 1 to 20 μM in 24 h treatment. In contrast, glycolytic inhibitors (gossypol, iodoacetic acid, 3-bromopyruvate, 2-deoxyglucose) and canonical chemotherapeutic drugs (paclitaxel, doxorubicin, cisplatin) were much less effective against BCSC viability (IC50> 100 μM). Conclusion: These results indicated that the use of some NSAIDs may be a promising alternative therapeutic strategy to target BCSC.
Keywords: celecoxib